Fisheries, international trade and sustainable development (The Centre GenevaCH, 2006)
Aims to help foster an inclusive and informed process for crafting multilateral, regional and domestic trade rules and policies in the fisheries sector that are supportive of sustainable development. Provides a comprehensive assessment of the complex set of trade policy issues and tools that bear on the sustainability and development of the fisheries sector.
Keywords: FISHERY